Clinical and pathogenesis interpretation of changes in the electrocardiogram in infectious diseases - Yu. P. Finogeev; S. M. Zacharenko; A. V. Semena (Журнал инфектологии, 2014)
Analyzing the diagnostic value of clinical and electrocardiographic diagnosis of heart lesions in infectious diseases should be emphasized that obtained with the help of their information is a benchmark for assessing not only the functional state of the myocardium of these patients. Importantly, according to the clinical manifestations and electrocardiogram in infectious diseases can be detected miokardidistrofiyu, myocarditis, as well as all possible rhythm disturbances, myocardial infarction, etc. The basis of circulatory disorders is a common factor in central nervous system (brain) as the most sensitive to the action of an infectious toxin. This, in turn, leads to dysfunction of the autonomic nervous system, since the latter is regulated by the cerebral cortex. Based on clinical experience revealed that approximately 15-20% of infectious patients during early convalescence, and especially of late convalescence there are various functional changes in the cardiovascular system, which at the height of the disease were not found. These changes include: painless myocardial ischemia, miokardidistrofiya, sick sinus syndrome, extrasystolic arrhythmia, early repolarization syndrome, a hyperfunction of the right atrium, incomplete block, right bundle branch block, etc.